Effect of co-infusion of dextrose-containing solutions on red blood cell haemolysis during packed red cell transfusion. Issue 1 (16th August 2011) - Stark, M J; Story, C; Andersen, C
Abstract : Aim: Transfusion guidelines prohibit co-infusion of maintenance intravenous fluid solutions, with significant consequences for neonatal clinical care. This study investigated co-infusion–related haemolysis in an in vitro model closely resembling clinical practice. Methods: Packed red blood cells (PRBCs, n=8) were co-infused at 5 and 10 ml/h with dextrose 5%, 10% and intravenous amino acid solution (synthamin). Free haemoglobin (fHb), as a measure of haemolysis, was measured by spectrophotometry and presented as % haemolysis and total fHb content (µmol/l). Results: Following co-infusion, there was no significant increase in PRBC haemolysis with either type of solution co-infused (p=0.82) or infusion rate (p=0.5). Neither macroscopic nor microscopic agglutination was observed during co-infusion for any type of solution co-infused. Conclusions: Co-infusion does not result in increased haemolysis, with total fHb significantly lower than currently accepted safe thresholds for fHb. Adherence to current guidelines may place undue restrictions on current transfusion practice in neonatal intensive care.